إمكانية تبني متطلبات الثقافة التنظيمية الخضراء وأثرها على تحسين جوانب المسؤولية البيئية للمؤسسة-دراسة حالة المؤسسة الوطنية للدهن ENAP وحدة سوق أهراس - سهام بيتور; منى سبيت (My University, 2022)
-This study to show the correlation and influence between the requirements of green organizational culture and responsibility. -This study contained two parts, the first part dealt with the theoretical aspect in which variables were dissected, the requirements of green organizational culture as an independent variable and environmental responsibility as a dependent variable. And for the second part, it the unit of Souk Ahras was devoted to the field study that was carried out at the National Institute of paint ENAP, where it was adopted the two research mainly distributed a questionnaire to a sample of 40 individual, and then retrieved 32 midwife forms for statiscal analysis, it was estimated at 80%. After the analysis process that was relied on the statiscal program spss, this study came to the following: - There is a perception and it became clear to the studied sample about the extent to which the requirements of green organizational culture and responsibility were adopted environmental in the enterprise may study. - The study showed that there is a positive correlation between the requirements of green organizational culture and environmental responsibility. - The study also showed that there is an influence relationship between the requirements of green organizational culture and environmental responsibility. ........................................................ هىدفت هذه الدراسة إلى تبيان العلاقة الارتباط والتأثير بين متطلبات الثقافة التنظيمية الخضراء والمسؤولية البيئية وقد احتوته هذه الدراسة على جزأين، الجزء الأول تناول الجانب النظري الذي تم في تشريح متغيرات الدراسة، متطلبات الثقافة التنظيمية الخضراء كمتغير مستقل. والمسؤولية البيئية كمتغير تابع. أما الجزء الثاني فقد خصص للدراسة الميدانية التي تمت في المؤسسة الوطنية للدهن وحدة سوق أهراس، حيث اعتمدت الباحثتان بشكل أساسي على توزيع استبيان على عينة مكونة من 40 فرد، وتم استرجاع 32 استمارة قابلة للتحليل الإحصائي بنسبة قدرت ب: %80 . بعد عملية التحليل التي تم الاعتماد فيها على البرنامج الإحصائي توصلت هذه الدراسة إلى: تصور واتضح لدى العينة المدروسة عن مدى تبني متطلبات الثقافة التنظيمية الخضراء والمسؤولية البيئية في المؤسسة قد الدراسة. - أظهرت الدراسة أن هناك علاقة ارتباط موجبة بين متطلبات الثقافة التنظيمية الخضراء والمسؤولية البيئية. - كما أظهرت الدراسة أن هناك علاقة تأثير بين متطلبات الثقافة التنظيمية الخضراء والمسؤولية البيئية.